If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(6d-5)=6d-1
We move all terms to the left:
4(6d-5)-(6d-1)=0
We multiply parentheses
24d-(6d-1)-20=0
We get rid of parentheses
24d-6d+1-20=0
We add all the numbers together, and all the variables
18d-19=0
We move all terms containing d to the left, all other terms to the right
18d=19
d=19/18
d=1+1/18
| 12a=80 | | 6x=15x-189 | | 6(x/2)=6(x/6+10)= | | 54a^2-9a-30=0 | | 55x-3(2x-12)=-64 | | 6(x/2)=6(x/6+10) | | (-1/9x)=-7 | | 55x-3x(2x-12)=-64 | | 2/4b+9/4=7/4 | | (-1/9)x=-7 | | 5.60+0.40x=10+0.20x | | 8p-7=10p-13 | | -5n+18+21n=32 | | 6+x/2=-12 | | 49x+9=49x83 | | 2x+45=15x+60 | | 3h+4h=h/60 | | -14-35=x^2 | | 6x-1=-4x+7 | | -7(x-16)=-56 | | U+17+7u+7+4u=180 | | X=180-(x+24) | | (x-12)x-6=-132 | | m/11-24=-18 | | (x-12)+-6=-132 | | m/10-14=-9 | | -8=6+a/4 | | 6x-8x+6=-2(x+2)+7 | | -6a+8a+14=a-6a | | a-6÷3=-7 | | m/4+8=-13 | | -8,3=d+4.7 |